Open Access and Library: the Postulates of Integration - Kozlenko, Denis G. (Bobcatsss, 2023)
Modern technologies turn the librarianship into a large-scale branch of the information industry; new practices allow transforming traditional functions of libraries, and new content appears in their basic technological processes. Today it is not enough for a librarian to know the exact location of a particular document in the collection of his library, he is obliged to navigate in the electronic collections of the world space. The idea of equal access to information and text, which is familiar and natural for libraries, continues to work in the new conditions. The availability of free online collections only increases the resource potential of the library. The article uses the bibliographic method, the bibliometric method, and the modelling method based on the analysis of publications on the topic and the experience of libraries to derive the main postulates of interaction between the Open Access initiative and library. It is noted that Open Access for scientists is a form of communication and a way to share the results of their experiments and research. Open Access performs a kind of fund-forming function for libraries, allows to fill in the gaps existing in the funds by legally accessing external resources. There are also such directions in providing libraries with readers’ access to open resources as systematization of information about open journals by library profile and providing the reader with links to open electronic platforms and journals; search for open articles in hybrid journals, etc. Open Access documents and data are of interest to libraries and library professionals as resources of scientific, educational and cultural significance. Due to the large-scale distribution of Open Access e- resources, their quality is not always unambiguous, so the preparation of appropriate guides or navigators may become relevant in the activities of libraries of all types. Methodological features of such navigators are determined by the inseparability of the unity of the bibliographic and electronic nature of the e-resources and are characterized by such attributes as: formalized description of the object, structured information, abstracts, auxiliary pointers, illustrative materials, hyperlinks, search bar, indication of the date of the last update. Such navigators for Open Access e-resources will be especially in demand for information and bibliographic support and support of educational and research developments in individual areas of knowledge, case study. As an example, the demand for and methodological features of preparing such information products for Open Access e-resources in radioelectronics is shown. Methodological products of libraries (recommendations, memos, etc.) on the search and use of Open Access e-resources, various training events may also be in demand. Undoubtedly, the Open Access initiative is a benefit for libraries and library specialists. The modern library accepts this phenomenon as a consultant, as a mentor and as a moderator.